The effect of using the Raft strategy in teaching writing skills to middle school students - Hussien, Ala'a Muhammed; Mousa, Manal Omar (Journal of Tikrit University for Humanities, 2024)
This practice represents an interactive co-evaluation activity among students, involving such elements as motivation, cooperation and collaborative work. It promotes meaningful learning experiences in a competitive environment. The goal of this activity is to examine topics which are explored during the semester through games that are created by students, as well as to promote holistic development and diversity through the investigation of a wide range of global cultures. Further, the activity seeks to enhance the internationalization of the pedagogic model that guides our collective educational philosophy. An empirical method of research is adopted in the current study which is based on observing students during an activity. Since the activity enhances students’ creativity for a better contextualization of the country to be presented. It replaces the traditional way of testing (the written tests) and gives the students the opportunity to see the level of the acquired learning in an interactive and fun context